2006
DOI: 10.1529/biophysj.105.078071
|View full text |Cite
|
Sign up to set email alerts
|

Protein Grabs a Ligand by Extending Anchor Residues: Molecular Simulation for Ca2+ Binding to Calmodulin Loop

Abstract: The structural difference in proteins between unbound and bound forms directly suggests the importance of the conformational plasticity of proteins. However, pathways that connect two-end structures and how they are coupled to the binding reaction are not well understood at atomic resolution. Here, we analyzed the free-energy landscape, explicitly taking into account coupling between binding and conformational change by performing atomistic molecular dynamics simulations for Ca2+ binding to a calmodulin loop. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 42 publications
(94 reference statements)
0
19
0
Order By: Relevance
“…Activation of the thin filament will be then precipitated by rotation and a re-opening of the hydrophobic pocket that can be envisioned as a reversal of the above described steps. The Ca 2+ ligands will reach [11] to grab and pull in the ion. The sidechain oxygen atoms of the site-terminal GLU and ligands 1, 3 and 5 will be attracted to the ion thus rotating the backbone, restoring the N 2 -OE 12 /N 9 -OE 12 interactions and inducing the B helix to move away from the A helix while unpacking the hydrophobic core.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the thin filament will be then precipitated by rotation and a re-opening of the hydrophobic pocket that can be envisioned as a reversal of the above described steps. The Ca 2+ ligands will reach [11] to grab and pull in the ion. The sidechain oxygen atoms of the site-terminal GLU and ligands 1, 3 and 5 will be attracted to the ion thus rotating the backbone, restoring the N 2 -OE 12 /N 9 -OE 12 interactions and inducing the B helix to move away from the A helix while unpacking the hydrophobic core.…”
Section: Resultsmentioning
confidence: 99%
“…EF-hand proteins have been the subject of several computational studies in recent years [10], [11], [12] and so has been another thin filament protein - actin. Deriu et al [13], [14] used atomistic and continuum scale modeling to describe the macro mechanics of actin filaments as a function of nanoscale events on the local level using molecular dynamics, coarse-grained model and normal mode analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The success of the grafting approach indicates that the loop itself, once structurally buttressed by the scaffold, is the functional motif, independent of other parts. Kobayashi and Takada [44] found that, at an early stage of binding, some key residue side chains extend their "arms" to catch Ca 2+ and, after catching, they carry the Ca 2+ to the center of the binding pocket. This grabbing motion results in smooth and stepwise exchange of the coordination partners of Ca 2+ from water oxygen to atoms in the CaM loop.…”
Section: Discussionmentioning
confidence: 99%
“…Using a molecular dynamics (MD) simulation of an all-atom model and explicit solvent molecules, Kobayashi and Takada found that the key residue that first catches the Ca 2+ ion is one of the two highly conserved acidic residues [44].…”
Section: Discussionmentioning
confidence: 99%
“…The EF-hand structure, which has a helix-loop-helix design, is the most common Ca 2ϩ -binding motif (30). AMBN has an EF-hand motif in the C-terminal region, and proteolytic peptides from that region, particularly those migrating at 27 and 29 kDa, can be seen on SDS-PAGE assays of calcium binding.…”
Section: Discussionmentioning
confidence: 99%